The Role of Nutrition in Managing Sarcopenia in Aging and Cancer - Wycik, Michał; Wądołowski, Artur; Kruk, Agnieszka; Łupińska, Marta; Stępień, Kamila; Kucińska, Julia; Chmielewski, Hubert; Przeniosło, Joanna; Komar, Julia; Kondratiuk, Gabriela (Quality in Sport, 2025)
Purpose of the research: This review aims to examine the role of nutrition and supplementation in the prevention and management of sarcopenia, particularly among the elderly and oncology patients. It explores how targeted dietary strategies can influence muscle mass, strength, and function. Materials and methods: The study is based on a review of the scientific literature, including clinical and experimental studies on nutritional interventions for sarcopenia in aging and cancer-related conditions. Results: Adequate protein intake, especially leucine-rich sources, alongside key nutrients such as vitamin D, omega-3 fatty acids, creatine, and antioxidants, has shown benefits in preserving muscle mass and improving physical function. In oncology patients, nutritional support is crucial to mitigate treatment-induced muscle loss and to improve therapy tolerance. Conclusions: Nutrition plays a vital role in mitigating sarcopenia and related complications in aging and cancer. Early screening and individualized nutritional strategies, combined with physical activity, offer a promising approach to improving patient resilience, treatment outcomes, and quality of life.